The psychology of music performance anxiety - Kenny, Dianna T. (Oxford : Oxford University Press, 2011)
Why are some performers exhilarated and energized about performing in public, while others feel a crushing sense of fear and dread, and experience public performance as an overwhelming challenge that must be endured? These are the questions addressed in this book, the first rigorous exposition of this complex phenomenon.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Music -- Performance -- Psychological aspects; Performance anxiety